Rare case of leiomyoma in Mayer-Rokitansky-Kuster-Hauser syndrome - Bhuyar, Sonal A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome is a cause for primary amenorrhea. It is characterized by the presence of XX karyotype, normal ovarian function and blind vaginal pouch. The uterus is usually represented by bilateral rudimentary primordia. Presence of functioning endometrial tissue may lead to development of hematometra in one or both primordia. Rarely myomas, neoplasms and adenomyosis can develop in the rudimentary bulbs. MRKH syndrome is frequently associated with urologic and skeletal abnormalities. In this case, a 45 year old patient presented with primary amenorrhea and lower abdominal pain. On examination, she had a blind vaginal pouch and a pelvic mass. She was investigated and taken for laparotomy with a provisional diagnosis of hematometra or ovarian tumor. The mass turned out to be leiomyoma in one of the rudimentary bulbs which was confirmed on histopathology. Our patient had vertebral abnormalities too. The incidence of MRKH syndrome is less and its association with pelvic tumor is even rarer. Hence this case is reported.